HUBUNGAN OBESITAS DENGAN PROFIL LIPID PADA REMAJA DI INDONESIA - Nuzuliyati Nurhidayati; Irlina Raswanti Irawan; Sudikno Sudikno (Persagi, 2022)
ABSTRACT The prevalence of obesity in the world shows an increase in both developed and developing countries, including obesity in adolescents. Obesity in children and adolescents can be a predictor of obesity in adulthood. Adolescents who are overweight have the potential to have higher lipid levels. This study aims to determine the relationship between obesity and lipid profile among adolescents in Indonesia. This study uses secondary data from Riskesdas 2013. The research design was cross-sectional. A sample of 2,921 adolescents aged 15-19 years had complete anthropometric data of height and weight, blood lipid examination results, gender, occupation, education, physical activity, consumption of fruit and vegetables, fat consumption, and smoking behavior. The results showed that the variables that were significantly related (p<0.05) to the lipid profile were obesity status, gender, age, area of residence, occupation, marital status, smoking behavior, and fat consumption. Based on obesity status, the three lipid profiles were statistically significant, namely total cholesterol (p=0.000), LDL cholesterol (p=0.000), and triglycerides (p=0.001), but not significant to HDL cholesterol (p=0.059). Obese adolescents have 1.92 times the risk of having high total cholesterol (>= 200 mg/dl) with 95% CI=1.36-2.72, 1.82 times the risk of having high LDL levels (>=130 mg/dl) with 95% CI=1.32-2.50, and 1.75 times risk of having high triglyceride levels (>=150 mg/dl) with 95% CI=1.26-2.44 compared to adolescents who are not obese. It can be concluded that obesity has a risk of increasing blood lipid levels in adolescents in Indonesia, namely total cholesterol levels, LDL cholesterol levels, and triglyceride levels, obesity does not contribute to HDL cholesterol levels. Keywords: obesity, overweight, adolescent, lipid profile ABSTRAK Prevalensi obesitas di dunia menunjukkan peningkatan baik di negara maju maupun berkembang, termasuk obesitas pada remaja. Obesitas pada anak dan remaja dapat menjadi prediktor terjadinya obesitas saat dewasa. Remaja yang memiliki berat badan lebih berpotensi untuk memiliki kadar lipid yang lebih tinggi. Penelitian ini bertujuan untuk mengetahui hubungan obesitas dengan profil lipid pada remaja di Indonesia. Penelitian ini menggunakan data sekunder Riskesdas 2013. Desain penelitian potong lintang (cross-sectional). Sampel berjumlah 2.921 remaja berumur 15-19 tahun memiliki kelengkapan data antropometri berupa tinggi badan dan berat badan, hasil pemeriksaan lipid darah, jenis kelamin, pekerjaan, pendidikan, aktivitas fisik, konsumsi buah sayur, konsumsi lemak, perilaku merokok. Hasil penelitian menunjukkan bahwa variabel yang berhubungan secara signifikan (p<0,05) terhadap profil lipid adalah status obesitas, jenis kelamin, umur, wilayah tempat tinggal, pekerjaan, status pernikahan, perilaku merokok dan konsumsi lemak. Berdasarkan status obesitas, ketiga profil lipid bermakna secara statistik yaitu kolesterol total (p=0,000), kolesterol LDL (p=0,000), dan trigliserida (p=0,001), namun tidak signifikan terhadap kolesterol HDL (p=0,059). Remaja yang obesitas berisiko 1,92 kali memiliki kolesterol total tinggi (>=200 mg/dl) dengan CI 95%=1,36-2,72, berisiko 1,82 kali memiliki kadar LDL tinggi (>=130 mg/dl) dengan CI 95%=1,32-2,50, dan berisiko 1,75 kali memiliki kadar trigliserida tinggi (>=150 mg/dl) dengan CI 95%=1,26-2,44 dibandingkan dengan remaja yang tidak mengalami obesitas. Dapat disimpulkan bahwa obesitas berisiko meningkatkan kadar lipida darah pada remaja di Indonesia, yaitu kadar kolesterol total, kadar kolesterol LDL dan kadar trigliserida, obesitas tidak memberikan kontribusi terhadap kadar kolesterol HDL. [Penel Gizi Makan 2022, 45(1):35-46]